Investigation in fuel cells using ' hydro-genius teach' - Muzamir, Isa (2004)
This thesis investigates the use of eco-friendly copper (I) iodide or cuprous iodide (Cul), a p-type semiconductor material, with the incorporation of a chelating agent or organic ligand, called tetramethylethylenediamine (TMED@TMEDA) in the preparation for solid-state dye-sensitized solar cells (DSSC). The Cul solution incorporated with the ligand was dispersed in acetonitrile solvent and deposited on glass and indium-doped tin oxide (ITO) substrates. The thin film is characterized to study its suitability for applications in dye sensitized solar cell (DSSC), a low cost solar cell but having high energy conversion efficiency. From the characterization, compared to that of pure Cul film, its optical properties show improved band-gap energy, while its electrical properties show improved conductivity. An efficient solidstate dye-sensitized solar cell (n-Ti02/dye/p-CuI) with improved stability was fabricated. The TMED-capped Cul crystals not only controls pore-filling of the dyed Ti02 layer but also improves the electrical contacts between the Ti02 particles, which in general improves the efficiency of the DSSCs. Current-voltage characteristics of the cell showed a larger energy conversion, achieving higher energy conversion efficiency and improved stability.